Does the Uncertainty of Monetary Policy Affect the Efficacy of Interest Rate Transmission Mechanisms? Micro-Evidence from the Investment-Capital Cost Sensitivity of Chinese Enterprises - Wang, Shenling; Jiang, Ling; Chang, Cai (International Journal of Global Economics and Management, 2024)
The uncertainty of monetary policy, as a latent cost of monetary policy regulation, increasingly captures the attention of the theoretical community and policy authorities worldwide. Employing empirical analysis on data from China's A-share non-financial listed companies between 2003 and 2019, it is found that monetary policy uncertainty undermines corporate confidence in development, leading to a diminished enthusiasm for adjusting investment strategies in response to economic fluctuations. This hampers the sensitivity of corporate investment to capital costs, suggesting that monetary policy uncertainty impedes market entity decision-making, not only impairing the effectiveness of monetary policy interest rate transmission mechanisms but also reducing the efficiency of corporate investment. Mechanism tests indicate that corporate confidence in development plays a crucial role in investment decisions in uncertain economic environments.